Mapping areal variation and majority language influence in North Sámi using hierarchical prosodic analysis - Hiovain, Katri; Suni, Antti Santeri; Simko, Juraj; Vainio, Martti Tapani (9th International Conference on Speech Prosody 2018, 2018)
We present results of a statistical hierarchical analysis of areal variation in prosody of spoken North Sámi languages. The hierarchical analysis method compares unigram models using cross-entropy measure. The models depict distributions of delta-features of f0 and energy signals decomposed using Continuous Wavelet Transform. These signals are obtained from speech recordings of five areal North Sámi varieties recorded in sites in northern Finland and Norway. We evaluate three potential sources of areal variation in prosodic characteristics of these five areal varieties: (1) traditional dialectal analysis of North Sámi, (2) influence of the relevant majority languages, and (3) geographical distance. Our results show a significant positive correlation between cross-entropy distances between models and geographical distances between recording sites, demonstrating a viability of the method for typological analysis. Prosodic characteristics of the areal varieties are also influenced by majority languages, and, to a smaller degree, by differences between the North Sámi dialectal varieties. Peer reviewed